SIMULASI UJIAN SELEKSI NASIONAL BERBASIS TES (SNBT) BAGI SISWA DARI 347 SMA - Meredita Susanty; Ludovika Jannoke; Weny Astuti; Tirta Rona Mayangsari; Harya Dwi Nugraha (Jurnal Abdi Insani, 2023)
The introduction of a new form of college entrance exam in 2023, coupled with the financial limitations of attending cram schools, poses a challenge for many high school students. To address this, Universitas Pertamina's community organized an exam simulation to familiarize students with the new exam format and enhance their ability to complete it effectively. The simulation event was announced on Instagram to engage a wider audience. Taking place online from January to June 2023 through the Moodle platform, the event attracted 327 participants from various high schools. Participant feedback highlighted a strong level of satisfaction with the website's usability, the quality of the provided questions, and the team's responsiveness to participants' inquiries.